2007
DOI: 10.1590/s0103-97332007000200023
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenology of infrared finite gluon propagator and coupling constant

Abstract: We report on some recent solutions of the Dyson-Schwinger equations for the infrared behavior of the gluon propagator and coupling constant, discussing their differences and proposing that these different behaviors can be tested through hadronic phenomenology. We discuss which kind of phenomenological tests can be applied to the gluon propagator and coupling constant, how sensitive they are to the infrared region of momenta and what specific solution is preferred by the experimental data.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…13 Indeed, the RGZ tree-level gluon propagator describes well the numerical data in the SU(2) case [64,92], for d ¼ 3 and 4, and in the SU(3) case [93] with d ¼ 4. It is also interesting to note that the fitting values for the dimension-two condensates are very similar for the SU(2) and SU (3) gauge groups in the four-dimensional case.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…13 Indeed, the RGZ tree-level gluon propagator describes well the numerical data in the SU(2) case [64,92], for d ¼ 3 and 4, and in the SU(3) case [93] with d ¼ 4. It is also interesting to note that the fitting values for the dimension-two condensates are very similar for the SU(2) and SU (3) gauge groups in the four-dimensional case.…”
Section: Introductionmentioning
confidence: 82%
“…3 These conditions can be given in terms of the value of the ghost dressing function F ðp 2 Þ ¼ p 2 Gðp 2 Þ at a given momentum scale p [22,31]. In particular, if one considers p ¼ 0, it is clear that 1=F ð0Þ ¼ 0 gives an IR-enhanced ghost propagator Gðp 2 Þ while 1=F ð0Þ > 0 yields a freelike behavior for Gðp 2 Þ at small momenta.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A discussion about the different solutions can be found in the introduction of Ref. [14], where the main references are also quoted. Only very recently it was claimed that a gauge invariant truncation of the QCD SDE can be obtained systematically [15].…”
Section: Introductionmentioning
confidence: 99%
“…A combination of analytical calculations, based on Dyson-Schwinger equations [1][2][3][4][5][6][7][8][9][10][11][12][13] and lattice gauge simulations , has given new insights into the behavior of QCD Green's functions. In particular, it has been found that in the Landau gauge at low momentum the ghost propagator is enhanced while the gluon propagator is suppressed.…”
Section: Introductionmentioning
confidence: 99%